Empowering Youth: the Impact of Basic Life Support (BLS) Training on Knowledge, Skills, and Attitude Development in Adolescents - Insana Maria; Annalia Wardhani (GLOBAL HEALTH SCIENCE GROUP, 2024)
The community, especially teenagers, really needs knowledge, attitudes and skills in providing Basic Life Support (BLS) so that first aid to victims of illness or accidents can be saved and avoid death. Objective: This study analyzes the effect of basic life support training using seminars, booklets, and video methods on increasing the knowledge, skills, and attitudes of teenagers in Syamsudin Noor Village. Method: This research uses a quasi-experimental design with a control design. The population in this study were teenagers in Syamsudin Noor Village, with a sample of 30 people from each group. The variables include teenagers' knowledge, skills and attitudes regarding BLS, as well as educational media in the form of videos on handling essential life support and booklets on handling critical life support. The instruments used in this research were questionnaires, observation sheets, and learning media. The analysis uses the t-test at a significance level of 5% (0.05). Results: There was an increase in teenagers' knowledge, attitudes and skills regarding essential life support. The results of analysis using the t-test obtained a p-value for each variable of knowledge (p=0.005), attitudes (p=0.004) and skills (p= 0.0014) after implementing BLS training. Conclusion: There is an effect of increasing the knowledge, attitudes and skills of teenagers in the community regarding essential life support after being given education through learning videos, seminars and booklets.